ROLE OF MODIFIED ULTRFILTRATION IN ADULT CARDIAC SURGERY: A PROSPECTIVE RANDOMIZED CONTROL TRIAL - Naveed, Danish; Khan, Riaz Anwar; Malik, Abdul; Ali Shah, Syed Zahid; Ullah, Ikram; Hussain, Amjad (Journal of Ayub Medical College Abbottabad, 2016)
Background: Cardiopulmonary bypass (CPB) is associated with morbidity and mortality. To reduce its adverse effect modified ultrafiltration is being increasingly employed. This study is planned to evaluate the benefits of modified ultrafiltration (MUF) in adult cardiac surgery. Methods: Eighty consecutive patients presenting to adult cardiac surgery as elective case were enrolled. These patients were randomly divided in to two groups. MUF group which received modified ultrafiltration after separation from CPB and control group which did not receive modified ultrafiltration. Postoperative mediastinal and chest drainage in 24 hrs, blood products requirement, reopening, ICU stay, and mortality in 30 days were recorded. These variables were compared between MUF group and control group. Results: Forty patients were randomized to control group and 40 in MUF group. Mean age was 51.15±8.90 in control group as compared to 46.95±13.24 MUF group (p=0.1). Out of 40 patients in control group 7 (17.5%) were female while 11 (27.5%) out of total 40 were female in MUF group. (p=.284). Mean CBP time was 120.62±20.97 in control group versus 117.37±38.78 in MUF group (p=0.64). Post-operative drain output ranged from 330 ml to 1300 ml in control group and 300 ml to 780 ml in MUF group. Mean postoperative drain output 554.25±192.57 in control group versus 439.22±89.59 in MUF group (p=.001). Three (7.5%) out of 40 patients required re-exploration in control group versus 1 (2.5%) in MUF group. (p=.305). Mean ICU stay was 52.80±22.37 hours in control group versus 45.30±21.82 hours in MUF group (p=0.133). Three (7.5%) out of 40 patients died in control group versus 1 (2.5%) in MUF group. (p=0.305). Conclusion: Use of modified ultrafiltration is associated with low postoperative bleeding less requirements of blood and blood products.